A strategic assessment of micro-hydropower in the UK and Irish water industry: Identifying technical and economic constraints. (September 2015) - Gallagher, J.; Harris, I.M.; Packwood, A.J.; McNabola, A.; Williams, A.P.
Abstract: Energy recovery using micro-hydropower (MHP) technology can enhance the sustainability of the water industry. This paper presents a structured four-step methodology for assessing potential energy recovery sites in water and wastewater infrastructure in regions of the UK and Ireland; at service reservoirs (SRVs), pressure reducing valves (PRVs) and wastewater treatment plants (WWTPs). Step 1 helped identify different all potential energy recovery sites in water and wastewater infrastructure. Step 2 shortlisted the most feasible sites for energy recovery, with the potential to generate an estimated 17.9 GWh per annum. Step 3 considered the technical and economic challenges relating to energy recovery and considered turbine selection, varying flow and site characteristics, feed-in tariffs (FITs) and overall project costs. Lastly, Step 4 provided evidence for the most feasible projects for Wales and Ireland based on capacity; larger than 3.6 or 18.2 kW at WWTP locations, 4.8 or 24.8 kW at PRVs and 12.8 or 22.2 kW at SRV sites, respectively. However, cheaper turbine technology and better financial incentives may improve the feasibility of smaller potential energy recovery sites. The results provide water companies with an estimated feasible capacity for potential energy recovery through MHP installations at different water and wastewater infrastructure sites. Graphical abstract: Highlights: 80 of the most feasible sites were identified with the potential to generate 17.9 GWh per annum. Two established turbine designs and a pressure control system were considered based on site requirements. Technical and economic challenges exist for MHP: varying flow conditions, feed-in tariffs (FITs) and overall project costs. Feasible sites in Wales/Ireland based on capacity: >3.6/18.2 kW at WWTPs; >4.8/24.8 kW at PRVs; 12.8/22.2 kW at SRVs. Cheaper turbine technology and better financial incentives may improve the feasibility of smaller potential energy recovery.